Analisis Penguatan Nilai Karakter Dalam Pembelajaran IPS di SMP Negeri 2 Petasia Timur Satu Atap Kabupaten Morowali Utara - Mohammad Iqbal; Elpisah Elpisah; Hartini Hartini (CV. Rayyan Dwi Bharata, 2026)
This study aims to: (1) describe teachers’ strategies in integrating character values into Social Studies learning, (2) identify the character values emphasized in Social Studies instruction, (3) analyze the challenges faced by teachers in reinforcing character values, and (4) examine students’ responses to character-based Social Studies learning at SMP Negeri 2 Petasia Timur One-Roof School, North Morowali Regency. This research employed a qualitative approach using a case study design. The research subjects consisted of a Social Studies teacher and seventh-grade students. Data were collected through semi-structured interviews and document analysis. Data analysis was conducted using the interactive model proposed by Miles and Huberman, supported by the ATLAS.ti software. The findings indicate that: (1) teachers systematically integrate character values through lesson planning, implementation, and evaluation by applying active learning methods, project-based learning, role modeling, and character habituation; (2) the character values emphasized include religiosity, nationalism, mutual cooperation, responsibility, and independence; (3) challenges in reinforcing character values originate from family environments, social environments, and internal school constraints; and (4) students demonstrate generally positive affective, cognitive, and behavioral responses, although continuous guidance is